A 3D Composite Model Using Electrospinning Technology to Study Endothelial Damage - Carmen Ciavarella; Luana Di Lisa; Gianandrea Pasquinelli; Maria Letizia Focarete; Sabrina Valente (Biomolecules, 2025)
Background: Endothelial dysfunction triggers atherosclerosis pathogenesis. This study aimed at developing a 3D scaffold model able to reproduce in vitro the human vascular intima and study the endothelial damage induced by oxidative low-density lipoproteins (ox-LDLs) and shear stress. (2) Methods: Three-dimensional sandwich-like scaffolds were fabricated using electrospinning technology, functionalized with type I collagen and laminin, and subsequently coated with methacrylated gelatin hydrogel (GelMa) to achieve the final composite structure. Human umbilical vein endothelial cells (HUVECs) were used as the cell model for testing the suitability of 3D supports for cell culture exposed to ox-LDL both under static and shear stress conditions. Cell viability, ultrastructural morphology, and nitric oxide (NO) levels were analyzed. (3) Results: Electrospun mats and their functionalization were optimized to reproduce the chemical and physical properties of the vascular intima tunica. The 3D supports were suitable for the cell culture. Ox-LDL did not affect the HUVEC behavior in the 3D models under a static environment. Conversely, high shear stress (500 µL/min, HSS) significantly decreased the cell viability, also under the ox-LDL treatment. (4) Conclusions: Endothelial cell cultures on electrospun supports exposed to HSS provide a candidate in vitro model for investigating the endothelial dysfunction in atherosclerosis research. Technical improvements to the experimental setting are necessary for validating and standardizing the suggested 3D model.